PAREDON P 1002 -ANGOLA: A VITORIA E CERTAI VICTORY IS CERTAIN! Songs of the Liberation Army of M.P.L.A. 12-inch mono L.P., with 16 page booklet edited by Pat Payandeh. Produced by Barbara Dane. "Recorded in the liberated zones by members of the Liberation Support Movement.” Paredon Records, P.O. Box 889, Brooklyn, N.Y. 11202, U.S.A. $4-50 in U.S. $5-00 elsewhere by I.M.O. - Bingham, Tom (International Library of African Music, 1973)
pages: 100
Keywords: African Music; Angola